Šķīrējtiesas nolēmumu piespiedu izpilde - Vargule, Zane (Latvijas Universitāte, 2012)
Šķīrējtiesām Latvijā ir neatkarīgas institūcijas statuss. Tomēr lai tam piemērotu piespiedu izpildi personām ir jāvēršas valsts tiesā ar pieteikumu par pastāvīgās šķīrējtiesas nolēmuma piespiedu izpildi, kas ir pretrunīgi esošajam civilprocesuālajam regulējumam. Turklāt darbā tiek vērtēts, cik ļoti Latvijā ir nepieciešamas neatkarīgas no valsts tiesām šķīrējtiesas statuss. Šim nolūkam darbā tiek aplūkota citu valstu pieredze jautājumā par šķīrējtiesas nolēmuma piespiedu izpildi. Lielākā atšķirība, kas vērojama, ir saistīta ar šķīrējtiesas nolēmuma atcelšanas iespējām.

Arbitrations in Latvia are independent institutions and awards made by them are final and binding. However, in order to apply enforcement on persons it is necessary to go before a national court with an application for an enforcement of permanent arbitration award, which is contradictory to the existing regulations of civil proceedings. Therefore this work evaluates approach of general jurisdiction of court judges on the issues of writ of execution arbitration award enforcement, analysis the ways of settling the question about the issue of an enforcement paper assess Latvian arbitration as potential independent from national courts. There is foreign countries experience as a base for analysis and assessments that help to conclude that expressed proposal are required to amend the civil procedure rules relating this field.
Compulsory Execution of an Arbitration Court Award
Keywords: Juridiskā zinātne